Difficulties in the Close Social Relationships of Slovenian Students during the Covid-19 pandemic - Melita Puklek Levpušček; Mojca Poredoš (Center for Educational Policy Studies Journal)
This study examined the difficulties experienced by Slovenian upper-secondary school and university students aged 18 to 25 in their close social relationships during the Covid-19 pandemic. We examined the extent of social difficulties in six domains (relationships with friends, establishing a new relationship with an intimate partner, sexuality, relationship with a current intimate partner, parental control and living with parents, and family conflict) in the pre-pandemic period and in the first two waves of the pandemic. We were also interested in whether demographic variables were related to the students’ perceived social difficulties. The results showed that the severity of reported difficulties increased in all six domains during the government-imposed quarantine periods, with relationships with friends and the opportunity to establish new intimate relationships being the most affected. In addition, we found differences in the extent of perceived difficulties related to educational status, gender, intimate relationship, and change in living situations. The study offers insight into the socio-emotional life of students during a non-normative life event that educators should acknowledge.